Characteristics of Graphene Like Material Synthesized from Commercial Activated Carbon of Coconut Shell Using a Modified Hummers Methods - Dewi Asaningsih Affandi; Norman Syakir, Fitrilawati (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2023)
Commercial activated carbon of coconut shell (CS) was used as the raw material for synthesis of graphene like material using modified Hummers method. The structure of carbon CS is amorphous and contains natural minerals such silica, potassium, magnesium and calcium as impurities. Prior to use, we carried out a thermal pre-treatment process (heating) on CS in order to remove the impurities. Pieces of CS were grounded to the size of 200 mesh (CS1), then heated at a temperature of 850°C with heating rate 5°C/min for 2 hours in a furnace. The obtained material was referred as CS2. A precursor of CS1 or CS2 were mixed with sulfuric acid solution until homogen in a glass beaker that placed in an ice bath. Then, potassium permanganate powder was slowly added into the solution while stirring. After that, distilled water and H2O2 were added into the solution to stop the oxidation process. The produced precipitate was passed through purification, ultrasonication and drying processes. The obtained material synthesized from CS1 is referred as H-CS1 and the one synthesized from CS2 is referred as H-CS2. The characterization results using FTIR, Raman, XRD and Uv-Vis show the obtained materials have charachteristic as reduced graphene oxide (rGO) with ID/IG = 1.0056 in H-CS1 and ID/IG ratio = 0.9476 in H-CS2. This result indicates that thermal pre-treatment process has lower impurity and defect on H-CS2